Essential oils of leaves and rhizomes of Kaempferia galanga Linn. (Chittagong University Journal of Biological Sciences, 2013)
Kaempferia galanga Linn. leaf and rhizome oils, obtained by hydrodistillation, were analyzed by gas chromatography mass spectroscopy (GC-MS). One hundred and eight components were identified in the leaf oil. The major components were linoleoyl chloride (21.42%), caryophyllene oxide (11.75%), cubenol (9.66%) and caryophyllene (5.60%). Eighty one components were identified in rhizome oil with the main components being 2-propenoic acid, 3-(4-methoxyphenyl),-ethyl ester (63.36%), ethyl cinnamate (6.31%), 4-cyclooctene -1-methanol (4.61%), caryophyllene oxide (4.37%) and limonene (3.22%). The compositions of both oils varied qualitatively and quantitatively. DOI: http://dx.doi.org/10.3329/cujbs.v3i1.13407 The Chittagong Univ. J. B. Sci.,Vol. 3(1&2):65-76, 2008